Distributivity as a Bridge Between Verb and Noun Domains in Standard Arabic - Khadija Farkad; Jamaa Ouchouid (Lingua : Journal of Linguistics and Language, 2026)
The interactions between the verbal and nominal domains exhibit recurrent structural patterns that make it possible to establish systematic correlations across categories. Events are mapped onto temporal intervals by means of a trace function, while their participants are integrated into the event structure through thematic-role assignment. Making these mappings explicit allows the analysis to constrain the space of possible interpretations, ruling out unattested outcomes while preserving the compositional derivation of complex predicates. The empirical investigation is based on six morphologically related verb forms in Standard Arabic, organized into three pairs that share the same lexical root but differ in their morphological realization, thereby enabling a controlled comparison in which lexical content is held constant and only morphosyntactic variation is tested. Methodologically, the study combines aspectual diagnostics, such as compatibility with temporal adverbials and the distinction between cumulative and quantized readings, with syntactic tests on argument realization, in order to determine how morphological variation affects both argument structure and event composition. The results show, first, that telicity does not systematically correlate with the definiteness or boundedness of the internal argument; second, that alternations within each morphological pair allow identical nominal complements to yield both telic and atelic readings; and third, that distributive interpretations consistently shift event structure toward atelicity by preventing the formation of a single bounded event, even in the presence of quantized objects.